The strange case of Dr. Jekyll & Mr. Hyde - Stevenson, Robert Louis; Jones, Rob Lloyd Tavares, Victor (Usborne London, 2010)
In the foggy alleys of Victorian London, Mr Utterson is seeking to uncover the secret of his friend and client, Dr Henry Jekyll. Just what is his connection to the vicious murderer Edward Hyde who stalks the city's streets at night?